Analysis of Resource Needs in South Banjarmasin District of Banjarmasin City - Rahmadani, Arif; Munawir, Abdillah (Universitas Ibn Khaldun Bogor, 2024)
This study aims to project and analyze facility needs in South Banjarmasin Subdistrict, Banjarmasin City. The need for adequate and efficient facilities has a significant impact on people’s daily lives and also has the potential to affect the economic growth and development of this area. Therefore, a comprehensive analysis is needed to identify the main needs that should be accommodated by public facilities and infrastructure. The research method used is a quantitative research method with an in-depth and comprehensive approach. The analysis used is to conduct a projection and analysis of facility needs. The hope is that this research will provide options for the Banjarmasin City government on facilities that need to be added to support community activities in South Banjarmasin Sub-district. The results show that there is a shortage of facilities for education, worship (especially mosques), health (such as posyandu and community treatment centers), and green open spaces (including playgrounds and cemeteries). These findings can serve as a basis for the government of Banjarmasin City in making policies and allocating appropriate resources to meet the needs of the facilities required by the community in South Banjarmasin Subdistrict.